Low profile external fixation using locking compression plate as treatment option for management of soft tissue problem in open tibia fracture grade IIIA: A case series - Hidayat, Luthfi; Triangga, Aditya Fuad Robby; Cein, Caesarean Rayhan; Irfantian, Ardicho; Rahayu, Bernadeta Fuad Paramita; Resubun, Alan Philips; Magetsari, Rahadyan (Elsevier, 2022)
Introduction: External fixators are the most common fixation method for fractures with substantial soft tissue compromise. Nonetheless, the frames used are bulky, uncomfortable, and cumbersome to patients. Using locking compression plate (LCP) as an external fixator (low profile external fixation/LPEF) owns the same properties as standard external fixators but may overcome disadvantages because of its low-profile frame. This case series aims to evaluate the results of LPEF for the management of tibia fracture with soft tissue compromise. Presentation of cases: We reviewed five patients at our centers who underwent surgery in 2020 with the appli- cation of LPEF. These patients had grade IIIA open tibia fracture with respective complications. The follow-up duration was 6 months post-operative in which we assessed Southampton Wound Assessment Scale (SWAS), laboratory infection markers, radiographic evaluation, and the Lower Extremity Functional Scale (LEFS). The results showed all wounds healed and cases with infection showed tendency of resolving, alongside varying degree of bone healing. The implant was well tolerated for patients and the functional outcome was overall good (mean LEFS: 71.26%). Discussion: The LPEF is fortuitously lightweight and more convenient for patients to ambulate, thus the compliance of early functional exercise is more likely to happen. Conclusion: Application of LPEF can be considered as an option for treating soft tissue compromised tibia fracture. In our experience, it is low profile, more acceptable to the patients, and displayed favorable outcomes especially in terms of soft tissue or skin healing and infection resolution.